2015
DOI: 10.1002/ppp.1876
|View full text |Cite
|
Sign up to set email alerts
|

Lithalsas in the Sentsa River Valley, Eastern Sayan Mountains, Southern Russia

Abstract: Perennial frost mounds identified as lithalsas occur in the Sentsa River valley of the Eastern Sayan Mountains, Russia. We report the first detailed study of permafrost in this region, based on analysis of the cryostructure and distribution of stable isotopes of oxygen and hydrogen, and ion concentrations from the ice‐rich cores of two lithalsas 3–7 m high. Their main cryostructures are reticulate and lenticular, with visible ice contents exceeding 50–60%. The vertical and lateral distribution of δ18О and δD v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The variation in δ 18 O values with depth in all boreholes is < 4 ‰ (Figure 5(a)) and, although values from the underlying clays are lower than those from upper sediments, the difference is not statistically significant. This finding is consistent with that of Iwahana et al (2012) andVasil'chuk et al (2015), who found small isotopic variations in lithalsas, which they attributed to an open system at the freezing front. Thus, although isotopic fractionation may occur across ice lenses (Calmels et al, 2008b), fractionation is not evident down-profile as it would be under closed-system conditions (Mackay, 1990;Lacelle, 2011).…”
Section: Stable Isotopessupporting
confidence: 92%
See 3 more Smart Citations
“…The variation in δ 18 O values with depth in all boreholes is < 4 ‰ (Figure 5(a)) and, although values from the underlying clays are lower than those from upper sediments, the difference is not statistically significant. This finding is consistent with that of Iwahana et al (2012) andVasil'chuk et al (2015), who found small isotopic variations in lithalsas, which they attributed to an open system at the freezing front. Thus, although isotopic fractionation may occur across ice lenses (Calmels et al, 2008b), fractionation is not evident down-profile as it would be under closed-system conditions (Mackay, 1990;Lacelle, 2011).…”
Section: Stable Isotopessupporting
confidence: 92%
“…() and Vasil’chuk et al . (), who found small isotopic variations in lithalsas, which they attributed to an open system at the freezing front. Thus, although isotopic fractionation may occur across ice lenses (Calmels et al ., ), fractionation is not evident down‐profile as it would be under closed‐system conditions (Mackay, ; Lacelle, ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the discontinuous permafrost zone, epigenetic permafrost often starts to form with the development of palsas or lithalsas, which may eventually transform into permafrost plateaus elevated above the initial ground surface by the accumulation of segregated ice. Palsas and lithalsas have been recently studied in Fennoscandia (Seppälä, ), the Altai and Sayan regions of Russia (Iwahana et al ., ; Y. K. Vasil'chuk et al ., ), the Northwest Territories (e.g. Wolfe et al ., ) and northern Quebec, Canada (Kuhry, ; Calmels and Allard, ; Calmels et al ., ), the Himalayas (Wünnemann et al ., ) and Mongolia (Sharkuu et al ., ).…”
Section: Permafrost Aggradationmentioning
confidence: 99%